Modified Non-Cultured Cell Spray Induced Epithelization in LAMB3 Mutation Epidermolysis Bullosa - Widhiati, Suci; Dewi, ShintaTrilaksmi; Yefta, Yefta; Danarti, Retno; Soebono, Hardyanto; Irmawati, Yulia Eka; Puspitasari, Monika; Trisnowati, Niken; Wibawa, Tri; Purnomosari, Dewajani; Wirohadidjojo, Yohanes Widodo (Dove Medical Press, 2022)
Background: Autologous non-cultured cell (ANCC) spray has been used to treat burns, chronic wounds, and vitiligo, but its use in junctional epidermolysis bullosa (JEB) has not been published previously. Chronic wounds in JEB are caused by mutations of laminin 332 (L322), whose function is to attach and act as a glue in the basal membrane. It is proposed that ANCC applications can provide keratinocytes and fibroblasts required to improve epithelization and spontaneously correct revertant keratinocytes in the wound area.